Structural Shifts of the Parvovirus B19 Capsid Receptor-binding Domain: A Peptide Study - Khrustalev, Vladislav V.; Stojarov, Aleksander Nicolaevich; Akunevich, Anastasia Aleksandrovna; Baranov, Oleg Evgenyevich; Popinako, Anna Vladimirovna; Samoilovich, Elena Olegovna; Yermalovich, Marina Anatolyevna; Semeiko, Galina Valeryevna; Sapon, Egor Gennadyevich; Cheprasova, Victoria Igorevna; Shalygo, Nikolai Vladimirovich; Poboinev, Victor Vitoldovich; et al. (Protein and Peptide Letters, 2024)
Background: Binding appropriate cellular receptors is a crucial step of a lifecycle for any virus. Structure of receptor-binding domain for a viral surface protein has to be determined before the start of future drug design projects. Objectives: Investigation of pH-induced changes in the secondary structure for a capsid peptide with loss of function mutation can shed some light on the mechanism of entrance. Methods: Spectroscopic methods were accompanied by electrophoresis, ultrafiltration, and computational biochemistry. Results: In this study, we showed that a peptide from the receptor-binding domain of Parvovirus B19 VP1 capsid (residues 13-31) is beta-structural at pH=7.4 in 0.01 M phosphate buffer, but alpha- helical at pH=5.0, according to the circular dichroism (CD) spectroscopy results. Results of infra- red (IR) spectroscopy showed that the same peptide exists in both alpha-helical and beta-structural conformations in partial dehydration conditions both at pH=7.4 and pH=5.0. In contrast, the peptide with Y20W mutation, which is known to block the internalization of the virus, forms mostly alpha-helical conformation in partial dehydration conditions at pH=7.4. According to our hypothesis, an intermolecular antiparallel beta structure formed by the wild-type peptide in its tetramers at pH=7.4 is the prototype of the similar intermolecular antiparallel beta structure formed by the corresponding part of Parvovirus B19 receptor-binding domain with its cellular receptor (AXL). Conclusion: Loss of function Y20W substitution in VP1 capsid protein prevents the shift into the beta-structural state by the way of alpha helix stabilization and the decrease of its ability to turn into the disordered state.
Keywords: sheet to helix transition